Integrating Network Pharmacology and Experimental Verification to Explore the Mechanism of Effect of Zuojin Pills in Pancreatic Cancer Treatment - Wang K; Miao X; Kong F; Huang S; Mo J; Jin C; Zheng Y (Dove Medical Press, 2021)
Kunpeng Wang,1 Xiongying Miao,2 Fanhua Kong,2 Siqi Huang,3 Jinggang Mo,1 Chong Jin,1 Yanwen Zheng2 1Department of General Surgery, Taizhou Central Hospital (Taizhou University Hospital), Taizhou, 318000, Zhejiang, People's Republic of China; 2Department of General Surgery, The Second Xiangya Hospital, Central South University, Changsha, 410011, Hunan, People's Republic of China; 3Department of Integrated Traditional Chinese & Western Medicine, The Second Xiangya Hospital, Central South University, Changsha, 410011, Hunan, People's Republic of ChinaCorrespondence: Yanwen ZhengDepartment of General Surgery, The Second Xiangya Hospital, Central South University, Changsha, 410011, Hunan, People's Republic of ChinaEmail zyw.1018@csu.edu.cnBackground and Aim: Pancreatic cancer is one of the most malignant tumors worldwide. Zuojin pills (ZJP), a traditional Chinese medicine (TCM) formula, which can treat a variety of cancers. However, the active compounds present in ZJP and the potential mechanisms through which ZJP acts against pancreatic cancer have not been thoroughly investigated.Methods: Data on pancreatic cancer-related genes, bioactive compounds, and potential targets of ZJP were downloaded from public databases. Bioinformatics analysis, including protein-protein interaction (PPI), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, was conducted to identify important components, potential targets, and signaling pathways through which ZJP affects pancreatic cancer. The results of this analysis were verified by in vitro experiments.Results: The network pharmacology analysis results showed that 41 compounds and 130 putative target genes of ZJP were associated with anti-pancreatic cancer effects. ZJP may exert its inhibitory effects against pancreatic cancer by acting on key targets such as JUN, TP53, and MAPK1. Moreover, KEGG analysis indicated that the anti-pancreatic cancer effect of ZJP was mediated by multiple pathways, such as the PI3K-AKT, IL-17, TNF, HIF-1, and P53 signaling pathways. Among these, the PI3K-AKT signaling pathway, which included the highest number of enriched genes, may play a more important role in treating pancreatic cancer. The in vitro results showed that ZJP significantly inhibits the cell cycle and cell proliferation through the PI3K/AKT/caspase pathway and that it can induce apoptosis of pancreatic cancer cells, consistent with the results predicted by network pharmacological methods.Conclusion: This study preliminarily investigated the pharmacological effects of ZJP, which appear to be mediated by multiple compounds, targets and pathways, and its potential therapeutic effect on pancreatic cancer. Importantly, our work provides a promising approach for the identification of compounds in TCM and the characterization of therapeutic mechanisms.Keywords: pancreatic cancer, Zuojin pill, network pharmacology, traditional Chinese medicine, proliferation, apoptosis